The Influence Of Green Transportation And Gen Z Consumer Behavior On The Selection Of Biskita Trans Pakuan Transportation Mode - Devka Salsabila; Syarief Gerald Prasetya (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Concern over sustainable transportation is growing as the demand for environmentally friendly alternatives increases. This study examines the impact of green transportation and Gen Z consumer behaviour as independent variables on the choice of transportation mode. The findings correspond with other studies, emphasizing the importance of green transportation and consumer behaviour in affecting the mode of transportation chosen. The purpose is to examine the direct correlation between green transport and the behaviour of Gen Z consumers, considering them as independent variables that impact the choice of transportation mode as the dependent variable. The sample comprised participants who had utilised Biskita transport on at least one occasion. They were residents of Bogor city, born between 1996 and 2010. The study aimed to investigate the influence of green transportation and Gen Z consumer behaviour on mode choice. Path analysis was conducted in order to understand the direct effects of relationship between variables. Data analysis was carried out using Smart PLS software. This study is constrained by the limited amount of available data and a small sample size of participants. The results is green transportation and gen z consumer behaviour have a significant direct influence on transport mode choice. Green transportation is critical in providing information that increases consumer awareness of environmental issues and enables consumer behaviour to better respond to external pressures and encourages consideration of environmental issues when making decisions on the mode of transport used and implementing actions that increase the likelihood of achieving optimal mode choice. Keywords: ; ; ;